EFEKTIVITAS PENERAPAN PENDEKATAN INQUIRY TERHADAP PENGUSAAN PENGETAHUAN SAINS TENTANG ALAM DAN LINGKUNGAN PADA ANAK USIA 5-6 TAHUN DI TK IT INSAN UTAMA 3 PEKANBARU - Nanda Oktavia Oktavia; Wilson '; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Based on the observation of the child's age 5-6 years in TK IT Insan Utama 3 Pekanbaru there are some children who do not understand the concept simple about symptoms that occur in the natural sciences and the surrounding environment. For example on a floating object, and drowning. When given questions about the sun or the land so many children do not understand the use fulness of natural objects, as well as on rainfall and its benefits. This means that children do not understand the science concepts contained in the surrounding well. The author also saw there were children who lack the interest and enthusiasm in participating in science learning activities given by the teacher. Related tothe phenomenon of learning activitie simplement edusing inquiry approach. This study aims to determine the effectiveness of inquiry approach to mastering scientific knowledge about nature and the environment in children aged 5-6 years in kindergarten IT Insan Utama 3 Pekanbaru. The sample used in this study 17 people. The data collection techniques were used that oral test. Data were analyzed usingt-test with SPSS ver 16.0. Research hypothesisis that there is a significant improvement on the mastery of scientific knowledge about nature and the environment in children after application of the inquiry approach. It can be seen from the analysis of data obtained t=-20.357 and p=0.000. Because p<0.05, it can be concluded that there was a significant improvement after using the inquiry approach to learning science. So it means that Ho is rejected and Ha accepted, which means there is a significant in crease between before and after the experiment with the inquiry approach. Key words: Knowledge Of Science, InquiryApproach